Electrochemical gradients are involved in regulating cytoskeletal patterns during epithelial morphogenesis in the Drosophila ovary - Weiß, Isabel (BMC Dev Biol, 2019)
BACKGROUND: During Drosophila oogenesis, the follicular epithelium differentiates into several morphologically distinct follicle-cell populations. Characteristic bioelectrical properties make this tissue a suitable model system for studying connections between electrochemical signals and the organisation of the cytoskeleton. Recently, we have described stage-specific transcellular antero-posterior and dorso-ventral gradients of intracellular pH (pH(i)) and membrane potential (V(mem)) depending on the asymmetrical distribution and/or activity of various ion-transport mechanisms. In the present study, we analysed the patterns of basal microfilaments (bMF) and microtubules (MT) in relation to electrochemical signals. RESULTS: The bMF- and MT-patterns in developmental stages 8 to 12 were visualised using labelled phalloidin and an antibody against acetylated α-tubulin as well as follicle-cell specific expression of GFP-actin and GFP-α-tubulin. Obviously, stage-specific changes of the pH(i)- and V(mem)-gradients correlate with modifications of the bMF- and MT-organisation. In order to test whether cytoskeletal modifications depend directly on bioelectrical changes, we used inhibitors of ion-transport mechanisms that have previously been shown to modify pH(i) and V(mem) as well as the respective gradients. We inhibited, in stage 10b, Na(+)/H(+)-exchangers and Na(+)-channels with amiloride, V-ATPases with bafilomycin, ATP-sensitive K(+)-channels with glibenclamide, voltage-dependent L-type Ca(2+)-channels with verapamil, Cl(−)-channels with 9-anthroic acid and Na(+)/K(+)/2Cl(−)-cotransporters with furosemide, respectively. The correlations between pH(i), V(mem), bMF and MT observed in different follicle-cell types are in line with the correlations resulting from the inhibition experiments. While relative alkalisation and/or hyperpolarisation stabilised the parallel transversal alignment of bMF, acidification led to increasing disorder and to condensations of bMF. On the other hand, relative acidification as well as hyperpolarisation stabilised the longitudinal orientation of MT, whereas alkalisation led to loss of this arrangement and to partial disintegration of MT. CONCLUSIONS: We conclude that the pH(i)- and V(mem)-changes induced by inhibitors of ion-transport mechanisms simulate bioelectrical changes occurring naturally and leading to the cytoskeletal changes observed during differentiation of the follicle-cell epithelium. Therefore, gradual modifications of electrochemical signals can serve as physiological means to regulate cell and tissue architecture by modifying cytoskeletal patterns.